Gender differences in post‐stroke functional outcome at discharge from an intensive rehabilitation hospital. (23rd February 2021) - Poggesi, Anna; Insalata, Greta; Papi, Gioele; Rinnoci, Valentina; Donnini, Ida; Martini, Monica; Falsini, Catuscia; Hakiki, Bahia; Romoli, Annamaria; Barbato, Carmen; Polcaro, Paola; Casamorata, Francesca; et al.
Abstract: Background: Gender differences in stroke functional recovery after rehabilitation are poorly investigated. Our aim was to compare functional outcomes at discharge from an intensive rehabilitation hospital after stroke in men and women, and to analyze their prognostic factors. Methods: Retrospective observational study of consecutive stroke patients discharged from an intensive neurological rehabilitation hospital, from January 2018 to June 2019. Modified Rankin Scale (mRS) at discharge was the main outcome measure. Results: Among the 208 included patients (mean age 73.4 ± 13.6 years), 105 (50.5%) were women. Women were significantly older (75.3 ± 13.8 vs. 71.4 ± 13.2 years, respectively, p = 0.041), and less often had a history of smoking habit (27% vs. 50%, p < 0.001). No gender differences emerged for vascular risk factors and comorbidities, pre‐stroke functional status, length of hospital stay, stroke type, and number of clinical deficits. At admission to the rehabilitation hospital, mRS score distributions were not different ( p = 0.795). At discharge, mRS score distributions and destinations did not differ between men and women ( p = 0.391, p = 0.785, respectively). A significant interaction between gender and the change in mRS score from admission to discharge was found ( F = 6.6, p = 0.011) taking into account age, stroke type, and number of initial clinical deficits. Dividing the cohort according to age, elderly women showed a better functional recovery compared to men. Conclusions: At admission to an intensive rehabilitation hospital, men and women presented a similar functional and clinical status and a substantial overlap of functional recovery after stroke. At higher ages, the potential for recovery appeared better in women compared to men. Abstract : Gender differences in recovery after stroke rehabilitation are poorly investigated. In our study on admission to rehabilitation hospital, men and women were clinically similar. Functional recovery was similar despite women being older than men. At higher ages, the potential for recovery appears better in women.